Oral involvement by Stevens-Johnson Syndrome associated with carbamazepine in an immunosuppressed patient: Case report - Hamasaki, Jean Teruo; Morato, Marcelo; Camargo, Rosana; Lima, Antonio Adilson Soares de (Journal of Oral Diagnosis, 2023)
INTRODUCTION: Stevens-Johnson syndrome (SJS) is caused by a delayed immune response triggered by the association of genetic and environmental factors. This reaction can be mediated mainly by some drugs. OBJECTIVE: The purpose of this article is to report the case of a patient with SJS associated with carbamazepine. CASE REPORT: A man was hospitalized complaining of odynophagia, whitish plaques in the mouth and swelling of the lips. Clinical examination revealed ulcerated and erosive lesions involving the buccal mucosa, lips, tongue and hard palate. The lips were swollen and with hemorrhagic crusts. Papular and purplish-colored lesions were observed on the skin. The patient reported that the lesions started 10 days ago, coinciding with the start of carbamazepine use. The diagnosis of SJS was established based on clinical information and the patient treated with support therapy. CONCLUSION: SJS is a clinical condition that affects the oral mucosa and can be triggered by the use of carbamazepine.